Chapter Ferroelectric Field Effect Control of Magnetism in Multiferroic Heterostructures - Vaz, Carlos A. F.; Ahn, Charles H. (InTechOpen, 2011)
Materials science
English
Keywords: Engineering thermodynamics; Technology, engineering, agriculture